Discovery of major QTL and a massive haplotype associated with cannabinoid biosynthesis in drug‐type Cannabis - Maxime deRonne; Davoud Torkamaneh (The Plant Genome)
Abstract Cannabis (Cannabis sativa L.), once sidelined by decades of prohibition, has now gained recognition as a multifaceted and promising plant in both medical research and commercial applications following its recent legalization. This study leverages a genome‐wide association study (GWAS) on 174 drug‐type Cannabis accessions from the legal Canadian market, focusing on identifying quantitative trait loci (QTL) and candidate genes associated with eleven cannabinoid traits using 282K common single‐nucleotide polymorphisms. This approach aims to transform our understanding of Cannabis genetics. We have pinpointed 33 significant markers that significantly influence cannabinoid production, promising to drive the development of Cannabis varieties with specific cannabinoid profiles. Among the notable findings is a massive haplotype of ∼60 Mb on chromosome 7 in Type I (i.e., tetrahydrocannabinol [THC]‐dominant) accessions, highlighting a major genetic influence on cannabinoid profiles. These insights offer valuable guidance for Cannabis breeding programs, enabling the use of precise genetic markers to select and refine promising Cannabis varieties. This approach promises to speed up the breeding process, reduce costs significantly compared to traditional methods, and ensure that the resulting Cannabis varieties are optimized for specific medical and recreational needs. This study marks a significant stride toward fully integrating Cannabis into modern agricultural practices and genetic research, paving the way for future innovations.